Incidence and predictors of mortality among TB-HIV co-infected individuals on anti-tuberculosis and anti-retroviral dual therapy in Northwest Ethiopia: A retrospective cohort study - Abebe Fenta; Tebelay Dilnessa; Destaw Kebede; Mekuriaw Belayneh; Zigale Hibstu Teffera; Bewket Mesganaw; Adane Adugna; Wubetu Yihunie Belay; Habtamu Belew; Desalegn Abebaw; Bantayehu Addis Tegegne; Zelalem Dejazmach; et al. (PLoS ONE, 2025)
Background Co-infection with the human immunodeficiency virus (HIV) and tuberculosis (TB) is a primary cause of death and morbidity. The rate of morbidity and death from TB-HIV is still Ethiopia’s top health issue. Objective This study aimed to assess the incidence and predictors of mortality among TB-HIV co-infected individuals on anti-TB and anti-retroviral dual Therapy at Debre Markos Comprehensive Specialized Hospital, Northwest Ethiopia. Methods A retrospective cohort study was conducted at the Debre Markos Comprehensive Specialized Hospital among 436 TB-HIV co-infected individuals. A computer-generated random sampling technique was used to select patient charts registered from September 1st, 2011, and August 31st, 2020. Epi-Data version 3.1 was used for data entry, and STATA version 13 was used for the analysis. The Kaplan-Meier survival curve was applied to estimate the cumulative survival time of the TB-HIV patients. Log-rank tests were utilized to compare the survival time across various categories of explanatory variables. Bi-variable and multivariable Cox proportional hazard models were fitted to find predictors of TB-HIV mortality. Results The mortality rate of TB-HIV co-infected individuals was 15.6%, with a median survival time of 42 months. Being male (Adjusted hazard Ratio (AHR)1.914;95%CI: 1.022–3.584), having CD4 count < 50 cells/mm3 (AHR 2.699; 95%CI: 1.220–5.973), being ambulatory (HR 2.794;95%CI: 1.459–5.352) and bedridden (AHR 5.514; 95%CI: 2.148–14.156), having low baseline weight (AHR 0.949;95%CI: 0.911–0.989), and having low hemoglobin level (AHR 0.927; 95%CI: 0.441–1.948) were important predictors for mortality. Conclusion and recommendation The mortality rate among TB-HIV co-infected patients at Debre Markos Comprehensive Specialized Hospital was high. Being male gender, having a CD4 count below 50 cells/mm³, being ambulatory and bedridden, having low baseline weight, and having low hemoglobin were the important predictors of mortality. To reduce mortality, it is crucial to focus on the early identification and management of high-risk patients, particularly those with low CD4 counts, poor functional status, and low hemoglobin. Strengthening integrated TB and HIV care services is recommended to improve patient survival outcomes.